ANALISA KEGAGALAN PADA DRILL PIPE DI RIG PDSI D1500/53 - Prakoso, Anggoro Tri; Suhardan, Suhardan; Homzah, Ozkar F; Hariadi, Sofwan (Universitas Tridinanti Palembang, 2018)
Oil and gas industry use drill pipe to make a well bore, the drill pipe conected one by one by operator.Drill pipe is the important tools to make the hole deeper to reach the resevoir. Another function of drill pipe is to trasnfer the mud and make the circulation during the drilling job. Non productive time on oil and gas drilling operation is undesirable for several reason. One of them is the economic, because it can increase cost, time, and decrase productitity. The problem that often happends is failiure of drill pipe. This paper is aimed to analize the charateristic faiulure on drill pipe in PDSI D1500/53 drilling rig. Material examination which have been done is tensile test, hardness test, spectometer test, fractography, and SEM EDX. The result shoed that fatigue and corrosion fatigue was the root cause of failiure.Â Keywords: Drill Pipe, Failure, Fatigue